To be a U.S. Secret Service agent - Holden, Henry M. (Zenith Press, 2006)
The Secret Service was established after the Civil War by the Treasury Department, originally to protect American currency against counterfeiters. After the assassination of President William McKinley in 1901, Congress directed the Secret Service to protect the President of the United States. Protection remains the primary mission of the United States Secret Service.It takes a special type of individual to be a U.S. Secret Service agent, one willing to "take a bullet" to preserve the ideals on which the United States was founded. "To Be a U.S. Secret Service Agent" lifts the curtain for a look inside this secretive law enforcement agency, including the highly selective recruiting, the intense training, and the specialized weapons and equipment used to protect current and past Presidents, Vice Presidents, their families, and visiting heads of state.